Trends in prevalence and incidence of type 2 diabetes among adults in Beijing, China, from 2008 to 2017. Issue 9 (17th January 2021) - Wang, Zijing; Wu, Yao; Wu, Junhui; Wang, Mengying; Wang, Xiaowen; Wang, Jiating; Wu, Tao; Wu, Yiqun; Hu, Yonghua
Abstract: Aims: To describe secular trends in diagnosed type 2 diabetes prevalence and incidence in Beijing, China. Methods: Using health insurance claims for 17.7 million adults ≥20 years in 2008–2017, we identified people with diabetes using hospital diagnoses and drug prescriptions. Results were age‐standardised using data for Beijing from China's 2010 census. Trends in prevalence and incidence were analysed using Joinpoint regression analysis. Results: From 2008 to 2017, we identified 2, 104, 159 people diagnosed with type 2 diabetes. Type 2 diabetes prevalence increased from 3.7% [95% CI: (3.6, 3.8)] to 6.6% (6.4, 6.7), but the annual rate of increase slowed from 18.1% (14.4, 22.0) to 1.5% (0.8, 2.2) before and after 2011 respectively. Women had a higher diabetes prevalence than men, for all years. The yearly increase in prevalence was greater in people younger than 40 years, with an average annual percentage change of 13.6% (10.7, 16.5) compared to 6.5% (5.6, 7.4) in those over 40 years. Over the 10 years, the overall incidence decreased from 24.3 (24.2, 24.4) to 11.5 (11.5, 11.6) per 1000 person‐years, but it increased in people younger than 40 years. The average age at diabetes diagnosis dropped from 62 to 56 years ( p  < 0.001). Among incident cases of diabetes, the percentage of people under 40 years increased from 3.0% to 10.9% ( p  < 0.001). Conclusions: The prevalence of diagnosed type 2 diabetes in Beijing increased continuously over the 10 years, the incidence decreased, except in people under 40 years. Continuous efforts are needed to prevent diabetes in China.